We've Got You Covered: Rebooting American Health Care - Chandra, Amitabh (Journal of Economic Literature, 2023)
Amitabh Chandra of Harvard University reviews “We’ve Got You Covered: Rebooting American Health Care” by Liran Einav and Amy Finkelstein. The Econlit abstract of this book begins: “Considers the objective and key elements of universal health insurance, presenting a blueprint for overhauling the US health-care system to guarantee essential medical coverage for everyone.”